THE DRUG ACTIVE INGRIDIENTS INDENTIFICATION IN THE LIGNIFIED STAMP PARTS OF HEMP - Іващенко, О. В.; Момот, Ю. В. (Scientific Progress & Innovations, 2014)
The article is devoted to an important issue: the research of the modern variety YUSO -31 hemp waste for active drug content. The cannabinoids determination in the lignified stamp parts of the cannabis plant (shive) was carried out by various methods. A microscopic morphological definition of the plant facility was carried out to prove its cannabis origin. The results of the tetrahydrocannabinol identification were also presented due to the qualitative chemical reactions and the quantitative analysis by gas chromatography.